OVERCOMING SOCIAL ISOLATION WITH DIGITAL TECHNOLOGIES AMONG AGEING POPULATIONS DURING COVID-19 - Reine, Ieva; Ivanovs, Andrejs; Mieriņa, Inta; Gehtmane-Hofmane, Ilona; Koroļeva, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
During Covid-19 social isolation has become more common worldwide, however, some groups, especially elderly people, might have experienced dramatically limited communication due to the lack of skills and access to digital technologies. In this paper, we examined if education was associated with the use of digital technologies to maintain contacts with a family, friends, other social networks and services. The survey was conducted in June-August 2020 by doing 1089 computer-assisted telephone interviews. The questions examined how people aged 50 years and older coped with socioeconomic and health-related impact of COVID-19.We used logistic regression analysis to study the association between the use of digital technologies and the level of education by gender and age. The higher the education was, the more it strongly associated with the use of digital technologies (OR 5.85; 95% CI 3.78-9.03). As expected, age was a strong explanatory factor, however, we did not find consistent age and gender differences. Among those who used digital technologies, analyses showed that overcoming social isolation was related to the education level. The conclusion of the study is that education has inevitable impact on the use of digital technologies and social contacts, however high education level is not crucial for the acquisition of information. It seems that digital technologies are important tools to prevent social isolation and are related to education that includes digital access and competencies.